2016
DOI: 10.1103/physrevc.94.014307
|View full text |Cite
|
Sign up to set email alerts
|

Identification of theJπ=1state inRa218populated viaα

Abstract: The α decay of 222 Th populating the low-lying J π = 3 − state, and also a proposed 1 − state, in 218 Ra has been observed. The observations suggest an excitation energy of 853 keV for the 1 − state, which is 60 keV above the 3 − state. The hindrance factors of these α decays give a possible boundary to the region of ground-state octupole deformation in the light-actinide nuclei. The relative positions of the J π = 1 − and 3 − states suggest they are produced by an octupole-vibrational mechanism, as opposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…The energy of the α particle emitted in the 220 Th → 216 Ra ground-state-to-ground-state decay has only previously been measured once, by Häusser et al in 1973 [7], where it was reported with a value of 8790 (20) keV. In that work, the half-life of the ground state of 220 Th was measured to be 9.7(6) μs.…”
Section: Previous Studiesmentioning
confidence: 88%
See 4 more Smart Citations
“…The energy of the α particle emitted in the 220 Th → 216 Ra ground-state-to-ground-state decay has only previously been measured once, by Häusser et al in 1973 [7], where it was reported with a value of 8790 (20) keV. In that work, the half-life of the ground state of 220 Th was measured to be 9.7(6) μs.…”
Section: Previous Studiesmentioning
confidence: 88%
“…The calibrations were carried out using known energies of α particles emitted from evaporation residues implanted into the DSSDs or in their decay chains. For the 18 20 Ne + 208 Pb experiment, the same α decays were used, with the exception of those from 220 Ra and 219 Ra. Due to more abundant statistics from the 18 O + 208 Pb experiment, αγ coincidences were studied; for that experiment, the absolute efficiency for the detection of γ rays in the focal-plane clover HPGe detectors was determined by comparing the numbers of α particles in the DSSDs with numbers of detected αγ coincidences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations